Hubungan Self Concept dan Self Confidence - Sholiha Sholiha; Lailatuzzahro Al-Akhda Aulia (Ilmu Psikologi Universitas Yudharta Pasuruan, 2020)
A confidence and an attitude toward a persons ability to accept both positive and negative that are shaped and learned through the process of studying with a view to his own happiness. While self concept is an idea, mind, feeling, belief and position known by the individual in relating to others. The purpose of this study is to know a self concept relationship with a self confident. The hypothesis of this study is there's a self concept relationship with a self confidence. In the study, researchers used a quantitative approach in an attempt to test hypotheses that had been drafted. The subject in this study is a teenager sitting in class 7 and 8 MTS miftahul ulum pandaan. The sampling technique used was staggerate stratified random sampling. The analysis of data in this study uses the scale of self concept and self confidence. Data analysis was calculated by using product moment Pearson and acquired rxy by 0.657 with an r-tab 1% of 0.254. Thus there is a highly significant correlation between self concept and a self confidence.